Pre- and post-pandemic knowledge of psychiatry: an assessment using the mhGAP basic course test - Sarabia, Silvana (2026)
Objective: To determine the level of knowledge about psychiatry among sixth-year medical students before and after the pandemic, using the Mental Health Gap Action Programme basic course test (mhGAP-BCT). Methodology: It was a descriptive, cross-sectional study. Sociodemographic data and responses to mhGAP-BCT were collected. Results: Students who completed an elective rotation in psychiatry scored higher on the mhGAP-BCT (β = 1.90; 95% CI [0.94, 2.87]; p < 0.001). Psychiatry knowledge scores using the mhGAP-BCT were lower in students during the 2022 period (post-pandemic) compared to the 2019 period (pre-pandemic) (14.44 ± 4.25 vs. 15.57 ± 1.89; p = 0.048). Conclusions: Students who completed an elective rotation in psychiatry achieved higher scores on the mhGAP-BCT. Post-pandemic mhGAPBCT scores were lower than pre-pandemic scores. To the best of our knowledge, this is the first attempt in our country to explore knowledge acquired by clerkship students using the mhGAP-BCT.